2013
DOI: 10.1038/ni.2758
|View full text |Cite
|
Sign up to set email alerts
|

The favorable IFNL3 genotype escapes mRNA decay mediated by AU-rich elements and hepatitis C virus–induced microRNAs

Abstract: The IFNL3 (IL28B) gene has received immense attention in the hepatitis C virus (HCV) field as multiple independent genome-wide association studies identified a strong association between polymorphisms near the IFNL3 gene and HCV clearance. However, the mechanism underlying this association has remained elusive. In this study, we report the identification of a functional polymorphism (rs4803217) located in the 3′ untranslated region (3′ UTR) of the IFNL3 mRNA that dictates transcript stability. This polymorphis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
148
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(156 citation statements)
references
References 52 publications
6
148
2
Order By: Relevance
“…We genotyped all samples (n = 33) for 3 genetic variants associated with HCV clearance: the intronic rs12979860-C/T (29,30) and exonic rs368234815-TT/ΔG (31,32) of IFNL4 and the 3′ untranslated region (UTR) rs4803217-T/G of IFNL3 (Supplemental Tables 1 and 5 and ref. 33). The majority of patients enrolled in the study were African-Americans, who are less likely to have the favorable genotypes CC, TT/TT, and GG at the rs12979860, rs368234815, and rs4803217 loci, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We genotyped all samples (n = 33) for 3 genetic variants associated with HCV clearance: the intronic rs12979860-C/T (29,30) and exonic rs368234815-TT/ΔG (31,32) of IFNL4 and the 3′ untranslated region (UTR) rs4803217-T/G of IFNL3 (Supplemental Tables 1 and 5 and ref. 33). The majority of patients enrolled in the study were African-Americans, who are less likely to have the favorable genotypes CC, TT/TT, and GG at the rs12979860, rs368234815, and rs4803217 loci, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Genotypes of IFNL4 variants (intronic rs12979860-C/T, previously known as the IFNL3 [IL28B] marker and exonic rs368234815-TT/ΔG) and a 3′ UTR IFNL3 variant (rs4803217-T/G) have been shown to affect treatment outcome for HCV infection and correlate with intrahepatic ISG expression, transcript stability of IFNL3, and balance of the innate immune system in response to HCV infection (28,31,33,(44)(45)(46). Although we genotyped these markers in our subjects (Supplemental Tables 1 and 5), the incidence of favorable IFNL3 and IFNL4 genotypes was too in- Statistical analysis of data in Figure 3C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A close association between TA length and the induction of the IL-28B gene has been reported in a Japanese population [76], but not in a South East Asian population, suggesting that ethnic differences may have some effect. Other investigators have reported that the stability of IL-28B transcripts may be influenced by the specific determining region in the 3 0 -untranslated region of the HCV genome [77].…”
Section: Subsets/bdca3 1 Dcs In Acute Hcv Infectionmentioning
confidence: 99%
“…The minor allele of a further SNP within exon 2, rs117648444, causes an amino acid substitution (P70S), leading to a functionally impaired IFNL4 protein. Transcription of IFNL3 has been shown to be related to rs12979860 [58] and ss469415590 [57], as well as to an SNP within the 3′-UTR which was shown to mediate miRNA-driven mRNA decay [60]. …”
Section: Interferonsmentioning
confidence: 99%